Optimizing EIL Using “Memrise” As A Builder Students’ Vocabularies - Melati Melati; Herlina Herlina (Edu-Ling: Journal of English Education and Linguistics, 2019)
Although the online English learning platform currently is interesting and entertaining and it can improve language acquisition, pronunciation, four integrated skills but it still becomes difficult to be used in English learning. Therefore, people must be mastering high technology to support their daily life and get much information instantly and accurately. In this article, the writer would like to introduce a suitable platform in English learning. English is considered as an international language (EIL) and the purpose is to facilitate communication of ideas, thoughts, feelings, knowledge, and culture, the language is a medium. Moreover, English can be taught by using Memrise Application in order to encourage students to learn English. train students in Communicative Competence and optimize the effectiveness of English Language Teaching. After reading this article, the writer expects that this article can help English teachers to apply this platform for English teaching in Indonesia. For this reason, teachers need to develop strategies that are appropriate to the characteristics of millennial students and be able to make it reach the competencies specified in the learning objectives. In this case, the use of media is also needed in innovative learning. Innovative learning using learning strategies and the use of media is very important to create effective English language learning, especially the current COVID-19 pandemic situation.